Knowledge, perception, and myths about COVID-19: A study from AIIMS, New Delhi - Souradeep Chowdhury; Radhika Sarda; Arvind Kumar; Anupam K Singh; H Vikas; Piyush Ranjan; Naveet Wig (Wolters Kluwer Medknow Publications, 2021)
Background: The COVID-19 pandemic has forced us to adapt to new habits, and to embrace a new normal. The authors wanted to conduct a study to gauge the public perception regarding the ongoing pandemic. Aims and Objectives: A single center cross-sectional study was conducted among hospital employees and their dependents attending the COVID screening outpatient department at a tertiary care hospital in Northern India, to gauge the knowledge, perception, and prevalent myths among the same. Methodology : For a set of 14 questions, the participants had a mean (standard deviation) score of 6 (2.14). Only 50 participants had adequate knowledge in all the three sections, namely knowledge, perception, and myths. Results : Our observation has been that the particular group we studied were still unaware of basic information such as transmission, clinical features, use of masks, and other key aspects about the ongoing pandemic. Conclusion : Extensive information campaigns and behavioral changes are needed to bring up the level of knowledge, particularly in hospital employees because they make an important subgroup in the community about creating a sense of awareness about the pandemic.